ANALISIS PENGARUH PERSEPSI HARGA, PROMOSI DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MOTOR MATIC MIO (Studi pada Konsumen Motor Matic Mio di Yamaha Mataram Sakti Semarang) - Situmorang, Gunanda; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2016)
The development of the motor industry is growing rapidly in Indonesia, where the demand of motorcycle is increasing every year. It also led the Â competition between motorcycle manufacturer in Indonesia. One sector that is experiencing tough competition is Â matic motorcycle, in this regard discuss Mio matic product. This study examines how perception influences the price, promotion and quality of product on purchasing decisions Mio motorcycle. The samples are people who have bought Mio matic motorcycle in Yamaha Mataram Sakti Semarang. The results showed that the factor of price and product quality has positive influence on purchase decisions. But the factor of promotion is not made a positive influence on the purchase decision.